Concretization of essence of the concept "health" as a methodological basis for the practice of healing the human body - Mikheenko O.І (Kharkov National Pedagogical University, 2013)
Basic descriptions, signs and factors of health of organism of a man are considered. Formulated definitions of concept "health". The ground of major signs is given, processes and phenomena which determine vital functions and predetermine the state of health. The holistic model of construction of organism is analysed. It is set that a health of man is a difficult multicomponent structure. It is well-proven that treatment can not be equated with making healthy. The complex of various facilities, directed on making healthy of corporalness, psychical, spiritual, cultural, social spheres of vital functions of man can provide most efficiency of health influence. It is marked that holistic approach is given by possibility it is correct to estimate the general state of man, role of health in his life and it is adequate to pick up the most effective methods of influence on an organism.